Marshall Performance Analysis Of Eggshells And Cement As Filler In Asphalt Concrete Mixtures (AC - WC) - Tisnawan, Rahmat; Rizki Ramadhan Husaini,; Ahmad Kurnain,; Rendi Saputra, (JIM - Journal International Multidisciplinary, 2024)
Roads are transportation infrastructure whose needs in Indonesia continue to increase, along with the increasing number of vehicles. Road construction is a construction that receives traffic loads, therefore it is expected that a road pavement layer must have a strong pavement construction and be able to receive loads from traffic users. AC-WC (Black-top Concrete - Wearing Course) asphalt layer is a road pavement construction consisting of asphalt composition, coarse aggregate, fine aggregate and filler. Fillers in asphalt mixtures function to increase the binding power of AC-WC asphalt, so as to improve mixture stability and fillers can fill the voids between aggregate particles, filler commonly used is stone ash. This research will be conducted with the addition of broiler eggshell filler and porland cement in the Asphalt Concrete wearing Course (AC-WC) mixture. The research was conducted with an experimental method conducted in the Civil Engineering laboratory of Abdurrab University. The specification used in this study is Public Road Revision 2 Year 2018, The optimum asphalt content (KAO) used was 6.5%. Based on the results of the study, the largest marshall stability and melting value is found in the 100% cement filler variation, which is 1772.7 Kg and the value of flow value (melting) 3.77 mm while the largest marshall quotient (MQ) value is found in the 25% eggshell filler variation, 75% cement, which is 529.2 Kg/mm.